Mutations and Binding Sites of Human Transcription Factors - Kamanu, Frederick K.; Medvedeva, Yulia A.; Schaefer, Ulf; Jankovic, Boris R.; Archer, John A.; Bajic, Vladimir B. (Frontiers in Genetics, 2012)
Mutations in any genome may lead to phenotype characteristics that determine ability of an individual to cope with environmental challenges. In studies of human biology, among the most interesting ones are phenotype characteristics that determine responses to drug treatments, response to infections, or predisposition to specific inherited diseases. Most of the research in this field has been focused on the studies of mutation effects on the final gene products, peptides, and their alterations. Considerably less attention was given to the effects of mutations on the regulatory mechanism(s) of gene expression, although these can also affect the phenotype characteristics. In this study we made a pilot analysis of the effects of mutations on the regulatory regions of 24,667 human RefSeq genes. Our study reveals that out of eight studied mutation types, ‘insertions’ are the only one that in a statistically significant manner overlap with transcription factor binding sites (TFBSs). We also find that 25 families of TFBSs have statistically significant enrichment of overlaps with mutations in the promoter regions we considered. The related transcription factors are, for example, prominent in processes related to intracellular signaling; cell fate; morphogenesis of organs and epithelium; development of urogenital system, epithelium and tube; neuron fate commitment. Our study highlights the significance of studying interactions of mutations within the genes regulatory regions and opens way for further detailed investigations on this topic, particularly on the downstream affected pathways.